The Development of Totor Gala Traditional Game Learning Video Using Nearpod Application for 4th Grade Elementary School Students - Atika Susanti; Nani Yuliantini; Andika Prabowo; Melisa Melisa; Tiara Andini; Ady Darmansyah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to develop “Totor Gala” traditional game learning video using the Nearpod application that are appropriate for elementary school students. The type of research in this research is Research and Development (R & D) with the Borg & Gall model of 7 of 10 steps. The research subjects were 4th grade students at Elementary School 41 Bengkulu City. The research instrument uses document analysis sheets, needs analysis sheets, validation sheets. The validation sheet is used to measure the feasibility of the video from the material and media aspects. Data collection techniques using document analysis, observation, questionnaires and tests. Data were analyzed through qualitative descriptive data and quantitative descriptive data analysis. The results of the research are in the form of learning videos of the Totor Gala game using the Nearpod application which contains material on cultural literacy and contemporary values. Media is suitable for use based on the validation results of material and media experts, as well as trials in schools with the "very valid" category. This product can be used as material for cultural literacy and the development of sportsmanship in 4th grade elementary school students.